Payment Digitalization And Its Impact On The Economy: An Inter-Regional Study In Indonesia - Dian Putri Maharani; Naziha Romiza; Ririn Nopiah (Economy and Finance Enthusiastic, 2025)
In recent years, economic transactions have been carried out digitally or cashless worldwide, including in Indonesia. This study aims to determine the impact of digital payments on economic growth through regional analysis in Indonesia during the COVID-19 pandemic. The data used is panel data from 34 provinces in Indonesia from 2019 to 2021. This study uses the multiple regression analysis method using the Eviews 12 program. The results show that digital payments have the greatest influence on the island of Sumatra, and have a significant positive effect on growth. economy. On the islands of Java-Bali, digital payments have no significant positive impact on economic growth. Meanwhile, on the eastern Indonesian island, digital payments do not affect economic growth. These findings suggest that government and policymakers should encourage the development of digital payment infrastructure and literacy, especially in regions where its impact on economic growth is still limited, so that the benefits of digitalization can be distributed more evenly across Indonesia.